1996
DOI: 10.1016/s0741-5214(96)70152-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of patient-related variables on the outcome of carotid endarterectomy

Abstract: Presenting symptoms significantly predict outcome after carotid endarterectomy. This should be considered both in patient selection and comparison of patient series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 27 publications
(1 reference statement)
2
57
0
1
Order By: Relevance
“…The low operative risk of stroke in patients with ocular ischemic events is consistent with the similarly low risk of stroke in those on medical treatment. 10,[25][26][27] The explanation for this good prognosis in patients with ocular ischemic events is uncertain, and evidence of particularly good collateral circulation toward the ipsilateral cerebral hemisphere is conflicting. [27][28][29] Many reports of the operative risk of CEA include a category of symptomatic indications that are generally called nonhemispheric.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low operative risk of stroke in patients with ocular ischemic events is consistent with the similarly low risk of stroke in those on medical treatment. 10,[25][26][27] The explanation for this good prognosis in patients with ocular ischemic events is uncertain, and evidence of particularly good collateral circulation toward the ipsilateral cerebral hemisphere is conflicting. [27][28][29] Many reports of the operative risk of CEA include a category of symptomatic indications that are generally called nonhemispheric.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported very high operative risks for urgent CEA for evolving symptoms, 10,11 whereas others have suggested that the risk is similar to that for stable symptoms. 12 However, the numbers of patients within individual studies are far too small to draw reliable conclusions.…”
Section: See Editorial Comment Page 2302mentioning
confidence: 99%
“…Patients included in the study either presented with focal neurological symptoms related to their anterior cerebral circulation (transient ischemic attack, amaurosis fugax, and stroke) within 6 weeks of surgery (defined as symptomatic) or presented with no history of neurological symptoms (defined as asymptomatic). 22 Patients with nonfocal, atypical, or distant neurological symptoms were excluded. Patients receiving angiotensin-converting enzyme inhibitors or angiotensin II blockers were excluded.…”
mentioning
confidence: 99%
“…34 Two of the angioplasty studies and 2 of the endarterectomy series did not separate patients presenting with TIA and stroke. 12,21,27,28 Excluding these studies, 58% of patients treated by angioplasty compared with 70% of patients undergoing endarterectomy presented with a TIA (Tables 1 and 3; 2 ϭ8.49, PϽ0.01).…”
Section: Presenting Symptomsmentioning
confidence: 99%